Pendugaan Parameter Genetik Populasi F3 dan F4 Tanaman Gandum Persilangan Oasis x HP1744 - Yamin, Mayasari; Efendi, Darda; Trikoesoemaningtyas, Trikoesoemaningtyas (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2015)
The study was aimed to obtain the information on the genetic diversity on agronomic traits of wheat among the F3 and F4 generations, derived from crosses of Oasis x HP1744, planted at the highland and medium elevation. The second objective was to acquire the character for selection and to acquire the adaptable genotypes on the highland and on the plain medium elevation. Selection was carried out using Shuttle Breeding, where F3 generation was selected at the Experimental Station of Cipanas (1100 m asl) and F4 generation was selected at the plain medium elevation of Cisarua (600 m asl). The experiment used Augmented Designs. Genetic material consisted of 57 F3 pedigree families selected from the F2 generation of Oasis x HP1744 cross plus six check varieties. The F4 generation cinsisted 320 selected genotypes from the F3 generation plus six check varieties. Plant height, flag leaf area, percentage of empty florets per panicle, number of grains/panicle and grain weight/panicle of the F3 generation showed larger mid value than the two parents. In the F4 generation, flag leaf greenness, total number of tillers, number of productive tillers, main panicle seed weight, number of seeds/panicle, seed weight/panicle, number of seeds/plant and seed weight/plant indicated the mean value larger than that of the Oasis. Plant height, number of productive tillers, days to flowering, maturity, spikelet number, and the total number of florets of the F4 generation showed higher heritability than that of F3 generation. Character suitable for indirect selection in the F3 was plant height, which indicated the best indirect differential selection. Potential families for further selection included: O/HP 21, O/HP 82, O/HP 12, O/HP 100 and O/HP 28. Characters most suitable for indirect selection in the F4 generation were: main panicle seed weight which indicated the best indirect differential selection. Genotypes potential for further selection in the medium elevation were O/HP82-19; O/HP82-15, O/HP78-5, O/HP49-30 and O/HP78-2.